2020
DOI: 10.1016/j.aimed.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vitamin C in the management of acute respiratory infection and disease: A rapid review

Abstract: Brief overview Current evidence from published systematic reviews indicate that oral intake of vitamin C may assist with symptoms of acute viral respiratory infections (ARI) by reducing fever and chills, relieving chest pain and assist in reducing symptoms of common cold-induced asthma. Intravenous (IV) vitamin C administration may reduce the need for vasopressor support and the duration of mechanical ventilations in critically ill patients in hospital. COVID-19 has similar signs and symptoms of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…Indeed, high bolus doses of vitamin D reduce its efficacy for non-classic effects while increasing adverse outcomes. The high efficacy of vitamin D supplements has only been detected among ARI patients with low baseline vitamin D status [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, high bolus doses of vitamin D reduce its efficacy for non-classic effects while increasing adverse outcomes. The high efficacy of vitamin D supplements has only been detected among ARI patients with low baseline vitamin D status [65].…”
Section: Discussionmentioning
confidence: 99%
“…A review assessing both safety and efficacy of vitamin C in the management of ARI and COVID-19 showed that vitamin C does aid in relieving the symptoms and respiratory functions; however, to date, high-quality clinical trials are needed to test its safety, and whether it should be supplemented orally or intravenously [45]. COVID-19 patients are being supplemented with doses that are higher than recommended, and it still remains to be confirmed whether or not supplements only control the short-term health risks of the disease [65]. The safety of vitamin C supplements has been reported for doses up to 2 g/day, with possible adverse effects starting at levels of 3-4 g/day.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence for an effect in the prevention and treatment of respiratory tract infections, such as the common cold, in the general population ( 33 ). A recent review concluded that, for individuals admitted to the hospital with community-acquired pneumonia, vitamin C may improve respiratory function in more severe cases, without any adverse effects ( 34 ). On the other hand, it should be noted that a recent study reported that treatment with high-dose zinc gluconate, ascorbic acid, or a combination of the 2 supplements did not significantly decrease the duration of COVID-19 symptoms compared with standard of care ( 31 ).…”
Section: Nutritional Support For Immunity In Older Adultsmentioning
confidence: 99%
“…Limfosit serta sel T CD4+, CD8+, dan CD3+ memiliki hubungan terhadap infeksi COVID-19, jika terjadi penurunan berarti pasien mengalami infeksi yang parah. Hal ini, dikarenakan terjadi penghambatan pada pertumbuhan dan apoptosis sel hematopoietic yang memproduksi antibodi autoimun (Zhang et al, 2020) dan sitokin tertentu (Schloss et al, 2020). Pemberian vitamin C dengan dosis tinggi dapat meningkatkan CD4+ yang lebih baik pada kelompok vitamin C dosis tinggi (intravena) dibandingkan dengan kelompok kontrol.…”
Section: Hasil Dan Pembahasanunclassified